2020
DOI: 10.3389/fendo.2020.00577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uric Acid-Lowering Treatment on Glycemia: A Systematic Review and Meta-Analysis

Abstract: Background: Serum uric acid levels have been shown to be associated with increased risk of diabetes. However, it remains unclear whether uric acid-lowering therapy (ULT) is associated with improved glycemic status. This study aimed to summarize evidence from randomized controlled trials (RCTs) to investigate whether ULT reduces fasting blood glucose (FBG) and glycated hemoglobin A1c (HbA1c) levels. Methods: PubMed, Embase, and the Cochrane Library were searched from inception until April 10, 2019. Moreover, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Studies show that treatment with allopurinol, a XO inhibitor, lowered A1C in T2D normotensive patients [ 32 ] and caused a decrease in markers of oxidative stress such as MDA in patients with T2D and mild hypertension [ 33 ]. However, a meta-analysis revealed that XO inhibition may have blood glucose-lowering effects only in individuals without T2D [ 34 ]. Consistent with our results, Kuppusamy et al [ 15 ] showed a strong positive association between A1C and serum XO in patients with T2D suggesting that poor glycemic control is associated with increased XO activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that treatment with allopurinol, a XO inhibitor, lowered A1C in T2D normotensive patients [ 32 ] and caused a decrease in markers of oxidative stress such as MDA in patients with T2D and mild hypertension [ 33 ]. However, a meta-analysis revealed that XO inhibition may have blood glucose-lowering effects only in individuals without T2D [ 34 ]. Consistent with our results, Kuppusamy et al [ 15 ] showed a strong positive association between A1C and serum XO in patients with T2D suggesting that poor glycemic control is associated with increased XO activity.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study from 8,678 patients with gout reports that uric acid-lowering therapy improves insulin resistance and reduces the incidence of T2DM ( Niu et al, 2018 ). However, a meta-analysis included six trials with 455 patients suggests that uric acid-lowering therapy with allopurinol may be effective at reducing glycemia, but such an improvement does not observed in patients with diabetes ( Chen et al, 2020 ) , suggesting that the significance of uric acid to T2DM might not be restricted to the incidence. It is therefore suspected that elevated SUA has some impact on the development and progression of complications associated with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Although we observed better performance of SUA in females, further evaluations of underlying hormonal and physiological assessments should be performed to evaluate a potential sexual dimorphism on the impact of SUA on whole‐body metabolism. Also, lowering SUA levels with allopurinol or other antihyperuricemics has had benefits on overall improvement on metabolic conditions, 32 so our study may provide a therapeutic goal to improve cardiometabolic health. Our study had some strengths and limitations.…”
Section: Discussionmentioning
confidence: 91%